A Scanning Electron Microscope Study of Fiowers of Carambola, Durian and Rambutan - Chin, H. F.; Phoon, A. C. G. (1982)
Fresh specimens of flowers of carambola (Averrhoa carambola L.), durian (Durio zibethinus Murr.) and rambutan (Nephelium lappaceum L.) were examined using the scanning electron microscope (SEM). Whole flowers and floral parts were described and illustrated in the micrographs. Floral structures and their differences within species were highlighted, their relationship and functions are discussed with special reference to pollination mechanisms and pollen morphology.